How the Tivaevae Model can be Used as an Indigenous Methodology in Cook Islands Education Settings - Te Ava, Aue; Page, Angela (The Australian Journal of Indigenous Education, 2020)
This paper explores an Indigenous research methodology, the tivaevae model, and its application within the Cook Islands education system. The article will argue that the cultural values embedded within its framework allow for the successful implementation of this Indigenous methodology. The model draws from tivaevae, or artistic quilting, and is both an applique process and a product of the Cook Islands. It is unique to the Cook Islands and plays an important part in the lives of Cook Islanders. The tivaevae model will be explained in detail, describing how patchwork creative pieces come together to create a story and can be used as a metaphor of the past, present and future integration of social, historical, spiritual, religious, economic and political representations of Cook Island culture. Further, the paper will then make links with the model to teaching and learning, by exploring secondary schools’ health and physical education policy and practices. Finally, the efficacy of the model in this context and its research implications will then be discussed.